Exploring the acoustic and prosodic features of a lung-function-sensitive repeated-word speech articulation test - Zeng, Biao; Williams, Edgar Mark; Owen, Chelsea; Zhang, Cong; Davies, Shakiela Khanam; Evans, Keira; Preudhomme, Savannah-Rose (Frontiers in Psychology, 2023)
Speech breathing is a term usually used when referring to the manner in which the expired air and lung mechanics are utilised for the production of the airflow necessary for phonation. Neurologically, speech breathing overrides the normal rhythms of alveolar ventilation. Speech breathing is generated using the diaphragm, glottis, and tongue. The glottis is the opening between the vocal folds in the larynx and is the primary valve between the lungs and the mouth and can vary the sound by varying its opening. Using voice as an indicator of health has been widely reported. The most common long-term respiratory disease is chronic obstructive pulmonary disease (COPD). The main symptoms of COPD are increasing breathlessness, a persistent chesty cough with phlegm, frequent chest infections, and persistent wheezing (NHS, 2020). There is no cure for COPD and is one of the leading causes of death in the world. The principal cause of COPD is tobacco smoking and estimates show that by 2030 COPD will become the third leading cause of death worldwide. The long-term aim is to study how speech generation, breathing, and lung function are linked in people with chronic respiratory diseases such as COPD. This pilot study has been designed to test an articulatory speech task, which uses a single word “helicopter” repeated multiple times to challenge speech-generated breathing and any breathlessness. This study in people with healthy lungs used a single-word articulation task to challenge respiratory system endurability via rapidly repeating the word “helicopter” for three 20-second runs interspersed with two 20-second rest periods of silent relaxed breathing. Acoustic and prosodic features were then extracted from the audio recordings of each adult participant. The pause ratio increased from the first run to the third, representing an increasing demand for breath. These data show that the repeated articulation task challenges speech articulation in a quantifiable manner which may prove useful in defining respiratory ill-health.